(untitled) (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
The purpose of this study was to describe students’ mathematical communication skills in solving mathematical problems on the material of two-variable linear equation system. This research uses a qualitative approach with descriptive research type. The subjects in this study were 3 students. Data collection techniques were in the form of tests and interviews. While data analysis techniques are done by reducing data, presenting data and drawing conclusions. Based on the results of the study, students with high mathematical ability were able to fulfil all three indicators of mathematical communication ability, while students with moderate mathematical ability were able to fulfil all three indicators of mathematical communication ability but there was an error from the subject due to the wrong number one and students with low mathematical ability could not fulfil all three indicators of mathematical communication ability